2005
DOI: 10.1017/s0021900200000887
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic baseline of the hazard rate function of mixtures

Abstract: In this article, we consider the limit behavior of the hazard rate function of mixture distributions, assuming knowledge of the behavior of each individual distribution. We show that the asymptotic baseline function of the hazard rate function is preserved under mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…, X n . There exist several results in the literature which show, under certain conditions, that the asymptotic behaviour, as t → ∞, of the failure rate function of a mixture is the same as the asymptotic behaviour of the failure rate of the strongest member of the mixture; see Block and Joe (1997), Block et al (2003), Hernandez (2004a), andLi (2005). Thus, we might expect similar results to hold forF in (3.1), although thatF is not a mixture of theF (1:i) , since some of the a i are negative.…”
Section: Results Based On Minimal Signatures and Path Setsmentioning
confidence: 99%
“…, X n . There exist several results in the literature which show, under certain conditions, that the asymptotic behaviour, as t → ∞, of the failure rate function of a mixture is the same as the asymptotic behaviour of the failure rate of the strongest member of the mixture; see Block and Joe (1997), Block et al (2003), Hernandez (2004a), andLi (2005). Thus, we might expect similar results to hold forF in (3.1), although thatF is not a mixture of theF (1:i) , since some of the a i are negative.…”
Section: Results Based On Minimal Signatures and Path Setsmentioning
confidence: 99%
“…They showed that the mixture failure rate for a family of exponential distributions with parameter ) , [ ∞ ∈ a α converges to the failure rate of the strongest population, which is a in this case. Block et al (1993), Block, Li and Savits (2003) and Li (2005) extended this to a general case.…”
Section: Section 5 Mixture Failure Rate For Large Tmentioning
confidence: 89%
“…Thus, we shall use the following property given in [18,20]. This result extends Lemma 2.5 in [15]. THEOREM 2.1: Let S be a survival function such that…”
Section: Preliminary Resultsmentioning
confidence: 78%